PENGARUH HEURISTIC DAN ISSUE VOTING TERHADAP PEROLEHAN SUARA PRABOWO SUBIANTO - SANDIAGA SALAHUDDIN UNO PADA PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2019 DI KOTA BOGOR : Array - Friantika Resti Karina; Dede Sri Kartini; Hendra (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
During the 2019 Presidential Election, the public could hardly avoid political exposure in the form of information & issues that even rolled around long before this election stage took place. This information / issue is used as material for voters to consider their choice. This is called issue voting, which consists of hard issues and easy issues. In addition, with the large amount of information / issues circulating, not a few people handle the excess information they have through heuristic means, one of which is by allowing other people outside of themselves to make decisions, which is called endorsement. Based on the results of the survey and the opinions of several observers, there are various reasons for Prabowo-Sandi winning in Bogor City. In this context, the main factors are issue and endorsement. This is the reason the author conducted a research entitled "The influence of heuristic and issue voting on Prabowo-Sandi's vote acquisition in Bogor City in the 2019 Presidential and Vice-Presidential Election". The method used in this research is a quantitative approach carried out by survey methods using factor analysis tests. The sampling technique in this study used a non-probability sampling technique, namely convenience sampling / accidental sampling technique. The analysis used for research data processing is factor analysis. Factor analysis aims to identify several factors that cause the correlation between a large number of variables and this technique is also classified as a reduction technique. The analysis results show that of the 9 (nine) indicators made, 3 (three) factors are formed. This is consistent with the initial mapping that was carried out as a research operation. The first factor, an easy issue with a loading factor of 0.904 and the acquisition of an impact dimension of 37.70%, means that symbolic things have the highest effect on the decision to elect Prabowo-Sandi voters in Bogor City. The second factor is the hard issue with a loading factor of 0.789 and the acquisition of a dimensional impact figure of 32.90%, meaning that technical matters such as work programs, presidential debates, and others have a second effect. While the last factor is the endorsement with a loading factor of 0.705 and the acquisition of a dimensional impact figure of 29.40%, which means that the consideration of recommendations from other parties who are considered worthy of being a role model (endorsement) has the lowest effect on the decision to vote for Prabowo-Sandi voters in Bogor City. On the other hand, according to the results of this study, it can be seen that in terms of endorsement for Prabowo-Sandi voters in the City of Bogor, they are considered to have a big role to be used as role models in choosing the presidential and vice presidential candidate pairs in 2019, namely religious figures.